Demonstration of relaxed InGaN-based red LEDs grown with high active region temperature. (30th September 2021) - Chan, Philip; Rienzi, Vincent; Lim, Norleakvisoth; Chang, Hsun-Ming; Gordon, Michael; DenBaars, Steven P.; Nakamura, Shuji
Abstract: Red LEDs were grown by metalorganic chemical vapor deposition with a high active region temperature of 870 °C on a relaxed InGaN/GaN superlattice buffer. The buffer was 100% biaxially relaxed by the thermal decomposition of an InGaN underlayer, measured by high resolution X-ray diffraction. Fabricated LEDs showed a low forward voltage of 2.25 V at a current density of 25 Acm −2 with no Al-containing layers in the active region, a peak emission wavelength of 633 nm at 200 Acm −2 and an on-wafer peak external quantum efficiency of 0.05%. Uniform red emission and relaxation were observed across a two inch substrate.